2016
DOI: 10.1097/aap.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Procedures to Relieve Chronic Knee Pain

Abstract: Radiofrequency treatments on the knee joint (major or periarticular nerve supply or intra-articular branches) have the potential to reduce pain from osteoarthritis or persistent postarthroplasty pain. Ongoing concerns regarding the quality, procedural aspects, and monitoring of outcomes in publications on this topic remain. Randomized controlled trials of high methodological quality are required to further elaborate role of these interventions in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 63 publications
0
45
0
7
Order By: Relevance
“…[18][19][20][21][22][23][24][25] The increasing number of publications concerning knee joint RFA is reflecting the growing clinical interest in this method. In a recent review of knee RFA denervation, Bhatia et al 26 concluded that the anatomical basis for radiofrequency cannula placement was often unclear. In addition, it was reported that most studies "did not utilize… sonoanatomical characteristics to improve the precision of RF cannula placement."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25] The increasing number of publications concerning knee joint RFA is reflecting the growing clinical interest in this method. In a recent review of knee RFA denervation, Bhatia et al 26 concluded that the anatomical basis for radiofrequency cannula placement was often unclear. In addition, it was reported that most studies "did not utilize… sonoanatomical characteristics to improve the precision of RF cannula placement."…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that most studies "did not utilize… sonoanatomical characteristics to improve the precision of RF cannula placement." 26 Thus, anatomically sound data regarding the articular branches and their courses amendable to intervention are paramount. Previous studies have focused on a limited number of articular branches except for Gardner 8 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…25 At this point, no evidence-based algorithm for the use of diagnostic blocks is available to properly select patients who might respond to partial anterior radiofrequency denervation of the knee. 26 Eligible patients in Choi and colleagues' investigation FIGURE 3. Visual analog scale scores (mean, 95% confidence interval) versus time, that is, before treatment (control) and at 1 month, 6 months, and 12 months following intervention.…”
Section: Discussionmentioning
confidence: 99%
“…There been a resurgence of interest in RF treatments for joint pain in the lower limbs secondary to degenerative pathologies. 15,16 However, several gaps remain in our knowledge and understanding of these procedures including indications, patient selection, technical parameters, anatomic targets, and longevity of benefit from RF procedures.…”
mentioning
confidence: 99%